The acute effects of preoperative ozone theraphy on surgical wound healing - Sahin,Hasan (2016)
ABSTRACT PURPOSE: To investigate the effects of preoperative rectal ozone insufflation on surgical wound healing over the proinflammatory cytokines and histopathological changes. METHODS: Twenty one rabbits were divided into 3 groups. Sham, surgical wound, and ozone applied (6 sessions, every other day 70 µg/mL in 12 mL O2-O3 mixture rectally) surgical wound groups were created. TNF-alpha and IL-6 levels from all rabbits were studied at the basal, 24th hour, and 72nd hour. The histopathological examination was done by removing the surgical scar tissue at the end of 72nd hour. RESULTS: TNF-alfa and IL-6 levels were significantly lower compared to the control group, in the rabbits treated with ozone. The increase in angiogenesis, the decrease in the number of inflammatory cells, epidermal and dermal regeneration, better collagen deposition, and increased keratinisation in stratum corneum were observed in the histopathological examination. It was determined that the wound healing noticeably accelerated in the ozone group. CONCLUSION: Preoperative rectal ozone insufflation had a positive effect on surgical wound healing in acute period.